The origin and biosynthesis of the naphthalenoid moiety of juglone in black walnut. Issue 1 (December 2018) - McCoy, Rachel; Utturkar, Sagar; Crook, Joseph; Thimmapuram, Jyothi; Widhalm, Joshua
Abstract Several members of theJuglandaceae family produce juglone, a specialized 1, 4-naphthoquinone (1, 4-NQ) natural product that is responsible for the notorious allelopathic effects of black walnut (Juglans nigra ). Despite its documented ecological roles and potential for being developed as a novel natural product-based herbicide, none of the genes involved in synthesizing juglone have been identified. Based on classical labeling studies, we hypothesized that biosynthesis of juglone's naphthalenoid moiety is shared with biochemical steps of the phylloquinone pathway. Here, using comparative transcriptomics in combination with targeted metabolic profiling of 1, 4-NQs in various black walnut organs, we provide evidence that phylloquinone pathway genes involved in 1, 4-dihydroxynaphthoic acid (DHNA) formation are expressed in roots for synthesis of a compound other than phylloquinone. Feeding experiments using axenic black walnut root cultures revealed that stable isotopically labeledl -glutamate incorporates into juglone resulting in the same mass shift as that expected for labeling of the quinone ring in phylloquinone. Taken together, these results indicate thatin planta, an intermediate from the phylloquinone pathway provides the naphthalenoid moiety of juglone. Moreover, this work shows that juglone can bede novo synthesized in roots without the contribution of immediate precursors translocated from aerial tissues. The present study illuminates all genes involved in synthesizing the juglone naphthoquinone ring and provides RNA-sequencing datasets that can be used with functional screening studies to elucidate the remaining juglone pathway genes. Translation of the generated knowledge is expected to inform future metabolic engineering strategies for harnessing juglone as a novel natural product-based herbicide. Bioengineering: revealing the genetic roots of a potential natural herbicide Revealing the synthetic pathway of the natural herbicide juglone paves the way for genetically engineered, weed-resistant crops. Juglone, belonging to the same molecular family as phylloquinone (also known as vitamin K1 ), is produced by plants, including black walnut and is generally toxic to nearby plant life. Until now, the genetic and synthetic basis of juglone remained unknown. Using genetic analysis, a research team from the United States' Purdue University, led by Joshua Widhalm, discovered that juglone is actually a product of the same synthetic pathway as phylloquinone and shares the same progenitor—a molecule called DHNA. This study partially reveals the genes responsible for juglone synthesis, and the authors suggest that the next step involves elucidating how the chemical is produced from DHNA. This discovery informs future efforts to engineer resilience into important crops.